Population assessment, distributional pattern and ethnomedicinal significance of Dactylorhiza hatagirea (D. Don) Soo: an endangered species of the Himalayan region - Thakar, Anil; Dave, Deeksha (Frontiers in Forests and Global Change, 2024)
Dactylorhiza hatagirea (D. Don) Soo, a perennial medicinal plant found in the sub-alpine and alpine zones of the Himalayas (2800–4,500 m), is critically endangered due its overharvesting and habitat degradation. The present study aimed at quantifying the population status, distribution, impact of anthropogenic disturbances and ethnobotanical applications of D. hatagirea in the Paddar Valley of North-western Himalaya. The research findings indicate the total density and frequency of 0.83 plants m−2 and 29.9%, respectively, which is comparatively lower than its associated 99 species belonging to 37 families. Observed decline in density, frequency, Importance Value Index (IVI) and spatial extent between 2022 and 2024, underscore the impact of habitat loss, over grazing and exploitation on the species. Principal Component Analysis (PCA) shows that the environmental factors like soil type and moisture, slope and aspect influence the distribution of D. hatagirea across the study sites. Correlation analysis reveals a positive relationship between species density and elevation, with optimal growth occurring at 3500–4000 m on moist, northeast facing slopes (r = 0.987). The well-drained, sandy and loamy soil with average moisture content was found to be more suitable for the species growth as compared to clayey soil. Regarding ethnobotanical value the research findings revealed that out of the 102 informants surveyed, 75% were aware of its medicinal properties, primarily using the tuberous roots to treat stomach ailments and enhance libido. However, 45% of respondents identified unsustainable utilization as a major threat, while 27% pointed to additional pressures from immature plant harvesting for its illegal trade and livestock grazing. These findings provide essential insights for decision makers regarding policy development and the involvement of local community for the conservation of D. hatagirea and related medicinal species in this ecologically sensitive region.